Segmented aliphatic polycarbonates which can incorporate unsaturated functional groups and methods for their preparation
Patent Information
- Application Number
- CN202411827583.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-12-12
AI Technical Summary
相应的,周期/分段等类型的共聚物则合成困难,几乎没有相关报道
[0025]This invention provides a segmented aliphatic polycarbonate with unsaturated functional groups, having the structure of Formula I. This polymer introduces polyester domains into a high-molecular-weight aliphatic polycarbonate structure for segmentation, transforming the polymer chain into a segmented structure, which can significantly adjust the polymer's mechanical properties.
Smart Images

Figure CN119638971B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer technology, and particularly relates to a segmented aliphatic polycarbonate that can be incorporating unsaturated functional groups and its preparation method. Background Technology
[0002] Developing and utilizing biodegradable polymers to replace traditional polyolefins is a hot topic in scientific research and society today. Large-scale application of biodegradable polymers can help alleviate "white pollution" and build a sustainable society. Polyesters, represented by polylactic acid and polycaprolactone, can biodegrade in natural environments and possess excellent mechanical and thermodynamic properties, making them widely used in disposable tableware, packaging materials, and tissue engineering. However, the simple composition of these polyesters limits the range of their performance adjustments, preventing them from replacing polyolefins in a wider range of applications. Carbon dioxide-based polycarbonate materials can be prepared by copolymerizing epoxides with CO2. These materials are also biodegradable and have advantages such as abundant monomer substitution structures, wide availability, and the use of CO2 as a C1 source, attracting considerable attention from researchers.
[0003] Synthesizing copolymers possessing both epoxide / CO2 copolymer segments and polyester segments can combine the advantages of both types of materials, achieving the goal of improving material properties and expanding application scenarios. However, the activities of different monomers vary greatly, and existing catalysts rarely possess the ability to simultaneously and efficiently copolymerize three monomers. Due to the differences in the polymerization reactivity among different monomers, the copolymerization reaction of three monomers under the action of homogeneous catalysts usually yields block copolymers, gradient copolymers, or random copolymers. Correspondingly, the synthesis of periodic / segmented copolymers is difficult, and there are almost no related reports. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide a segmented aliphatic polycarbonate that can be incorporating unsaturated functional groups and a method for preparing the same. The polymer is segmented by introducing polyester domains on the basis of high molecular weight aliphatic polycarbonate, thereby transforming the polymer chain into a segmented structure, which can significantly adjust the mechanical properties of the polymer.
[0005] This invention provides a segmented aliphatic polycarbonate with unsaturated functional groups that can be introduced, having the structure of Formula I:
[0006]
[0007] R1 is selected from the substituents on the side chains of epoxy compounds shown in Formulas 101 to 108 after ring-opening copolymerization with dioxane or cyclic anhydrides:
[0008]
[0009] The structure of R2 is formed by the ring-opening of a cyclic anhydride and an epoxy compound;
[0010] Both n and m are non-zero natural numbers.
[0011] Preferably, the cyclic anhydride is selected from any one of compounds 1 to 26:
[0012]
[0013]
[0014] Preferably, the segmented aliphatic polycarbonate has a structure of formula I-1 to formula I-6:
[0015] Preferably, in the segmented aliphatic polycarbonate, each anhydride-epoxy unit is a minimal structural domain;
[0016] The minimum structural domain content is 1–20 wt%.
[0017] Preferably, the glass transition temperature of the segmented aliphatic polycarbonate is 32–42°C.
[0018] This invention provides a method for preparing segmented aliphatic polycarbonate with incorporating unsaturated functional groups as described in the above-mentioned technical solution, comprising the following steps:
[0019] An epoxy compound, a cyclic anhydride monomer, CO2, a solvent, and a heterogeneous catalyst surface catalyst are mixed and polymerized to obtain a segmented aliphatic polycarbonate with the structure of Formula I.
[0020] Preferably, the heterogeneous catalyst is selected from one or more of zinc glutarate, metal-supported zinc glutarate, and bimetallic cyanide;
[0021] The molar mass ratio of the heterogeneous catalyst to the epoxide compound is 1:200 to 1000.
[0022] Preferably, the pressure of the CO2 is 0.5 to 3.5 MPa.
[0023] Preferably, the polymerization temperature is 50–120°C and the polymerization time is 6–48 h.
[0024] Preferably, the molar ratio of the anhydride monomer to the epoxide compound is 0.025 to 0.5:1.
[0025] This invention provides a segmented aliphatic polycarbonate with unsaturated functional groups, having the structure of Formula I. This polymer introduces polyester domains into a high-molecular-weight aliphatic polycarbonate structure for segmentation, transforming the polymer chain into a segmented structure, which can significantly adjust the polymer's mechanical properties. Attached Figure Description
[0026] Figure 1 The 1H NMR spectrum of the polycarbonate prepared in Example 1 of this invention;
[0027] Figure 2 The 1H NMR spectrum of the polycarbonate prepared in Example 4 of this invention;
[0028] Figure 3 The 1H NMR spectrum of the polycarbonate prepared in Example 6 of this invention;
[0029] Figure 4 The 1H NMR spectrum of the polycarbonate prepared in Example 7 of this invention;
[0030] Figure 5 The 1H NMR spectrum of the polycarbonate prepared in Example 8 of this invention;
[0031] Figure 6 The image shows the 1H NMR spectrum of the polycarbonate prepared in Example 9 of this invention. Detailed Implementation
[0032] This invention provides a segmented aliphatic polycarbonate with unsaturated functional groups that can be introduced, having the structure of Formula I:
[0033]
[0034] R1 is selected from the substituents on the side chains of epoxy compounds shown in Formulas 101 to 108 after ring-opening copolymerization with dioxane or cyclic anhydrides:
[0035]
[0036] The structure of R2 is formed by the ring-opening of a cyclic anhydride and an epoxy compound;
[0037] Both n and m are non-zero natural numbers.
[0038] This invention precisely controls the polymer structure by using the theoretically smallest structural domain (a single anhydride-epoxy unit), which can significantly improve the elongation at break of aliphatic polycarbonate materials with the introduction of a small amount of anhydride monomer.
[0039] In this invention, the cyclic anhydride used to form the R1 or R2 substituent is selected from any one of compounds 1 to 26:
[0040]
[0041]
[0042] The segmented aliphatic polycarbonate described in this invention has structures of formulas I-1 to I-6:
[0043]
[0044]
[0045] The segmented aliphatic polycarbonate provided by this invention has a single anhydride-epoxy unit as the minimum structural domain; the content of the minimum structural domain is 1-20 wt%, and the corresponding polymer has a relative molecular mass of 100-600 kDa, n = 5-30, and m = 300-1800; in specific embodiments, the content of the minimum structural domain is 7%, 1%, 4%, 9%, 6%, or 3%. The glass transition temperature of the segmented aliphatic polycarbonate is 32-42℃; the maximum tensile strength is 4-36 MPa, and the elongation at break is 10-1100%, and for the same type of material, a 1% change in the structural domain content can achieve an 80% change in the elongation at break.
[0046] This invention provides a method for preparing segmented aliphatic polycarbonate with incorporating unsaturated functional groups as described in the above-mentioned technical solution, comprising the following steps:
[0047] An epoxy compound, a cyclic anhydride monomer, CO2, a solvent, and a heterogeneous catalyst surface catalyst are mixed and polymerized to obtain a segmented aliphatic polycarbonate with the structure of Formula I.
[0048] The present invention preferably carries out the above reaction in a high-pressure reactor. The present invention utilizes a heterogeneous catalyst surface catalyst chain transfer method to segment the polymer. In this process, due to differences in monomer activity, the anhydride cannot be continuously inserted, forming a single anhydride-epoxy unit as the smallest structural domain.
[0049] The heterogeneous catalyst used in this invention is selected from one or more of zinc glutarate (ZnGA), metal-supported zinc glutarate (ZnGA / MY, where M is a metal ion and Y is an anion), and bimetallic cyanide (DMC). In a specific embodiment, the heterogeneous catalyst is a ZnGA / NaCl catalyst. The molar ratio of the heterogeneous catalyst to the epoxide compound is 1:200 to 1000. In a specific embodiment, the molar ratio of the heterogeneous catalyst to the epoxide compound is 1:500. The CO2 pressure used in this invention is 0.5 to 3.5 MPa. In a specific embodiment, the CO2 pressure is 2 MPa. The solvent used in this invention is selected from one or more of toluene, xylene, tetrahydrofuran, dichloromethane, dichloroethane, n-hexane, and 1,4-dioxane.
[0050] The epoxy compounds described in this invention are consistent with the range of epoxy compounds shown in Formulas 101 to 108 above; the range of cyclic anhydride monomers is consistent with the cyclic anhydrides shown in Compounds 1 to 26 above. The molar ratio of the cyclic anhydride to the epoxy compound is 0.025 to 0.5:1; in specific embodiments, the molar ratio of the cyclic anhydride to the epoxy compound is 1:10, 1:20, 1:40, or 1:5. In specific embodiments, the epoxy compound is selected from propylene oxide or styrene oxide; the cyclic anhydride is selected from 1,2-cyclohexanediol, phthalic anhydride, maleic anhydride, or succinic anhydride.
[0051] In this invention, the polymerization temperature is 50–120°C, and the polymerization time is 6–48 hours. In a specific embodiment, the polymerization temperature is 70°C, and the polymerization time is 24 hours.
[0052] To further illustrate the present invention, the following detailed description, in conjunction with embodiments, provides a segmented aliphatic polycarbonate capable of incorporating unsaturated functional groups and its preparation method, but these descriptions should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] Propylene oxide (29.7 g) was added to a high-pressure reactor, along with a ZnGA / NaCl catalyst (0.2 g) at a molar ratio of 1:500 to propylene oxide, and phthalic anhydride (7.58 g) at a molar ratio of 1:10 to propylene oxide. The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. This segmented polymer was added to ethanol (200.0 g) to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0055]
[0056] Sampling 1¹H NMR analysis showed that the minimum structural domain (phthalic anhydride-epoxy) content was 7%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 39℃, a maximum tensile strength of 35.0 MPa, and an elongation at break of 11%.
[0057] Example 2
[0058] Propylene oxide (29.7 g) was added to a high-pressure reactor, along with a ZnGA / NaCl catalyst (0.2 g) at a molar ratio of 1:500 to propylene oxide, and phthalic anhydride (3.89 g) at a molar ratio of 1:20 to propylene oxide. The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0059]
[0060] Sampling 1 ¹H NMR analysis showed that the minimum structural domain (phthalic anhydride-epoxy) content was 3%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 39℃, a maximum tensile strength of 9MPa, and an elongation at break of 320%.
[0061] Example 3
[0062] Propylene oxide (29.7 g) was added to a high-pressure reactor, along with a ZnGA / NaCl catalyst (0.2 g) at a molar ratio of 1:500 to propylene oxide, and phthalic anhydride (1.95 g) at a molar ratio of 1:40 to propylene oxide. The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. This segmented polymer was added to ethanol (200.0 g) to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0063]
[0064] Sampling 1 ¹H NMR analysis showed that the minimum structural domain (phthalic anhydride-epoxy) content was 1%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 39℃, a maximum tensile strength of 36MPa, and an elongation at break of 40%.
[0065] Example 4
[0066] Propylene oxide (29.7 g) was added to a high-pressure reactor, along with a ZnGA / NaCl catalyst (0.2 g) at a molar ratio of 1:500 to propylene oxide, and succinic anhydride (3.85 g) at a molar ratio of 1:10 to propylene oxide. The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0067]
[0068] Sampling 1 ¹H NMR analysis showed that the minimum structural domain (succinic anhydride-epoxy) content was 4%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 36℃, a maximum tensile strength of 20MPa, and an elongation at break of 410%.
[0069] Example 5
[0070] Propylene oxide (29.7 g), ZnGA / NaCl catalyst (0.2 g) with a molar ratio of 1:500 to propylene oxide, and succinic anhydride (7.49 g) with a molar ratio of 1:5 to propylene oxide were added to a high-pressure reactor. Carbon dioxide was introduced at 2 MPa, and the reactor was heated to 70 °C and reacted for 24 h to obtain a segmented polymer. The segmented polymer was added to ethanol (200.0 g) to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0071]
[0072] Sampling 1 H NMR analysis showed that the minimum structural domain (succinic anhydride-epoxy) content was 7%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 32℃, a maximum tensile strength of 8MPa, and an elongation at break of 1100%.
[0073] Example 6
[0074] Propylene oxide (29.7 g) was added to a high-pressure reactor, along with a ZnGA / NaCl catalyst (0.2 g) at a molar ratio of 1:500 to propylene oxide, and maleic anhydride (3.80 g) at a molar ratio of 1:10 to propylene oxide. The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. This segmented polymer was added to ethanol (200.0 g) to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0075]
[0076] Sampling 1H NMR analysis showed that the minimum structural domain (maleic anhydride-epoxy) content was 8%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 39℃, a maximum tensile strength of 20MPa, and an elongation at break of 400%.
[0077] The sample can be crosslinked by Michael addition in the following conditions: sample: ethylenedithiol: triethylamine = 15:1:1.
[0078] Example 7
[0079] 29.7 g of propylene oxide was added to a high-pressure reactor, along with 0.2 g of ZnGA / NaCl catalyst (molar ratio 1:500 to propylene oxide) and 7.58 g of 1,2-cyclohexane (molar ratio 1:10 to propylene oxide). The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. This segmented polymer was added to 200.0 g of ethanol to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0080]
[0081] Sampling 1 ¹H NMR analysis showed that the minimum structural domain (1,2-cyclohexanediol-epoxy) content was 3%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 39℃, a maximum tensile strength of 33MPa, and an elongation at break of 400%.
[0082] Example 8
[0083] 61.4 g of styrene oxide, 0.2 g of ZnGA / NaCl catalyst (molar ratio of 1:500 to propylene oxide), and 7.58 g of phthalic anhydride (molar ratio of 1:10 to propylene oxide) were added to a high-pressure reactor. The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. The segmented polymer was added to 200.0 g of ethanol to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0084]
[0085] Sampling 1 ¹H NMR analysis showed that the minimum structural domain (phthalic anhydride-epoxy) content was 7%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 49℃, a maximum tensile strength of 56.0 MPa, and an elongation at break of 6%.
[0086] Example 9
[0087] 78.8 g of furfuryl glycidyl ether was added to a high-pressure reactor, along with 0.2 g of ZnGA / NaCl catalyst (at a molar ratio of 1:500 to propylene oxide) and 7.58 g of phthalic anhydride (at a molar ratio of 1:10 to propylene oxide). The reactor was then purged with 2 MPa of carbon dioxide, heated to 70 °C, and reacted for 24 h to obtain a segmented polymer. This segmented polymer was added to 200.0 g of ethanol to precipitate the polymer. The precipitate was filtered, collected, and dried to obtain the material with the following structure:
[0088]
[0089] Sampling 1 ¹H NMR analysis showed that the minimum structural domain (phthalic anhydride-epoxy) content was 6%. After sample preparation, thermodynamic properties were tested, with a glass transition temperature of 32℃, a maximum tensile strength of 16.0 MPa, and an elongation at break of 60%.
[0090] As can be seen from the above embodiments, the present invention provides a segmented aliphatic polycarbonate with unsaturated functional groups, having the structure of Formula I. This polymer introduces polyester domains to segment the polymer chain based on a high molecular weight aliphatic polycarbonate, transforming the polymer chain into a segmented structure, which can significantly adjust the mechanical properties of the polymer.
[0091] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A segmented aliphatic polycarbonate incorporating unsaturated functional groups, wherein n and m are both non-zero natural numbers. The segmented aliphatic polycarbonate has structures of formulas I-1 to I-6: Formula I-1; Formula I-2; Formula I-3; Equation I-4; Formula I-5; Formula I-6; In the segmented aliphatic polycarbonate, a single anhydride-epoxy unit is the smallest structural domain; The minimum structural domain content is 1~20wt%; the relative molecular mass of the polymer is 100-600 kDa; The glass transition temperature of the segmented aliphatic polycarbonate is 32~42℃.
2. A method for preparing the segmented aliphatic polycarbonate of claim 1, which can introduce unsaturated functional groups, comprising the following steps: An epoxy compound, a cyclic anhydride monomer, CO2, a solvent, and a heterogeneous catalyst surface catalyst are mixed and polymerized to obtain segmented aliphatic polycarbonates with structures of formulas I-1 to I-6.
3. The preparation method according to claim 2, characterized in that, The heterogeneous catalyst is selected from one or more of zinc glutarate, metal-supported zinc glutarate, and bimetallic cyanide; The molar mass ratio of the heterogeneous catalyst to the epoxide compound is 1:200~1000.
4. The preparation method according to claim 2, characterized in that, The pressure of the CO2 is 0.5~3.5 MPa.
5. The preparation method according to claim 2, characterized in that, The polymerization reaction temperature is 50~120℃, and the polymerization reaction time is 6~48h.
6. The preparation method according to claim 2, characterized in that, The molar ratio of the anhydride monomer to the epoxy compound is 0.025~0.5:1.
Citation Information
Patent Citations
Terpolymerization of carbon dioxide, epoxide and cyclic anhydride
KR1020150106642A